Medo e direitos no governo dos obedientes: notas sobre a cultura despótica brasileira e argentina - Passetti, Edson (Ecopolítica, 2014)
Passados 50 anos do golpe de Estado que instalou a ditadura civil-militar no Brasil, o artigo procura situar o contraste entre as práticas de resistências anarquistas e a mobilização golpista de 1964. Situa o medo e o silêncio da massa seguidora do pastorado de Estado e sua conduta reativa no Brasil e na Argentina. Palavras-chave: ditadura, cultura despótica, massa. ABSTRACT: Fifty years after the coup d’État which established the civil-military dictatorship in Brazil, this articles seeks to place the contrast between the anarchist practices of resistance and the 1964’s coup mobilization. The text registers the fear and silence of the mass which followed the state pastorate and its reactive conduct in Brazil and Argentina. Keywords: dictatorship, despotic culture, mass.